Infant negative reactivity defines the effects of parent–child synchrony on physiological and behavioral regulation of social stress. (6th October 2015) - Pratt, Maayan; Singer, Magi; Kanat-Maymon, Yaniv; Feldman, Ruth
Abstract: How infants shape their own development has puzzled developmentalists for decades. Recent models suggest that infant dispositions, particularly negative reactivity and regulation, affect outcome by determining the extent of parental effects. Here, we used a microanalytic experimental approach and proposed that infants with varying levels of negative reactivity will be differentially impacted by parent–infant synchrony in predicting physiological and behavioral regulation of increasing social stress during an experimental paradigm. One hundred and twenty-two mother–infant dyads (4–6 months) were observed in the face-to-face still face (SF) paradigm and randomly assigned to three experimental conditions: SF with touch, standard SF, and SF with arms' restraint. Mother–infant synchrony and infant negative reactivity were observed at baseline, and three mechanisms of behavior regulation were microcoded; distress, disengagement, and social regulation. Respiratory sinus arrhythmia baseline, reactivity, and recovery were quantified. Structural equation modeling provided support for our hypothesis. For physiological regulation, infants high in negative reactivity receiving high mother–infant synchrony showed greater vagal withdrawal, which in turn predicted comparable levels of vagal recovery to that of nonreactive infants. In behavioral regulation, only infants low in negative reactivity who received high synchrony were able to regulate stress by employing social engagement cues during the SF phase. Distress was reduced only among calm infants to highly synchronous mothers, and disengagement was lowest among highly reactive infants experiencing high mother–infant synchrony. Findings chart two pathways by which synchrony may bolster regulation in infants of high and low reactivity. Among low reactive infants, synchrony builds a social repertoire for handling interpersonal stress, whereas in highly reactive infants, it constructs a platform for repeated reparation of momentary interactive "failures" and reduces the natural tendency of stressed infants to disengage from source of distress. Implications for the construction of synchrony-focused interventions targeting infants of varying dispositions are discussed.